3D imaging of shark egg cases (Palaeoxyris) from Sweden with new insights into Early Jurassic shark ecology. (3rd July 2021) - Krüger, Ashley; Slater, Sam; Vajda, Vivi
ABSTRACT: Several shark species produce egg cases as protective casings in which their embryos develop. These casings are composed of multiple layers of collagen and are extremely durable, making them prone to fossilisation. Here we document Palaeoxyris ( Spirangium ) ‒ fossil shark egg cases from Lower Jurassic successions of southern Sweden. We present high-resolution 3D images of Palaeoxyris based on microfocus X-ray computed tomography (μCT) of seven specimens, including fossils that were embedded within a sandstone matrix. Our examination of the internal structure of the egg cases revealed the possible remnants of a yolk and foetus in one specimen. The cases were most likely produced by hybodont sharks, as outlined in previous studies, and the occurrence of hybodont teeth from Lower Jurassic successions of Sweden support this. Palynological analysis of the matrix from one of the specimens hosting Palaeoxyris, indicates an early Hettangian age. The high percentage of spores (c. 60%) reveals that the egg cases were laid during the Transitional Spore Spike Interval following the end-Triassic mass extinction. The egg cases are found in conjunction with fossil horsetails; with the broader palynological and sedimentological evidence, this suggests an estuarine depositional setting, and potentially indicates that newborn sharks were living in habitats comparable to modern mangroves, as is often the case today.